A Fast, Reliable Oil-In-Water Microemulsion Procedure for Silica Coating of Ferromagnetic Zn Ferrite Nanoparticles Capable of Inducing Cancer Cell Death In Vitro - Stefan Nitica; Ionel Fizesan; Roxana Dudric; Lucian Barbu-Tudoran; Anca Pop; Felicia Loghin; Nicoleta Vedeanu; Constantin Mihai Lucaciu; Cristian Iacovita (Biomedicines, 2022)
The applications of ferrimagnetic nanoparticles (F-MNPs) in magnetic hyperthermia (MH) are restricted by their stabilization in microscale aggregates due to magnetostatic interactions significantly reducing their heating performances. Coating the F-MNPs in a silica layer is expected to significantly reduce the magnetostatic interactions, thereby increasing their heating ability. A new fast, facile, and eco-friendly oil-in-water microemulsion-based method was used for coating Zn0.4Fe2.6O4 F-MNPs in a silica layer within 30 min by using ultrasounds. The silica-coated clusters were characterized by various physicochemical techniques and MH, while cytotoxicity studies, cellular uptake determination, and in vitro MH experiments were performed on normal and malignant cell lines. The average hydrodynamic diameter of silica-coated clusters was approximately 145 nm, displaying a high heating performance (up to 2600 W/gFe). Biocompatibility up to 250 μg/cm2 (0.8 mg/mL) was recorded by Alamar Blue and Neutral Red assays. The silica-coating increases the cellular uptake of Zn0.4Fe2.6O4 clusters up to three times and significantly improves their intracellular MH performances. A 90% drop in cellular viability was recorded after 30 min of MH treatment (20 kA/m, 355 kHz) for a dosage level of 62.5 μg/cm2 (0.2 mg/mL), while normal cells were more resilient to MH treatment.